The Rationale Behind a Continous Nasal Positive Airway Pressure Machine That Approximates the Nasal Cycle During Sleep - (:unkn) unknown (MedCrave, 2017)
Normal nasal airflow alternates in dominance between the two nostrils with an ultradian rhythm called the “nasal cycle.” The nasal cycle is thought to enable the patent airway to perform the majority of the air-conditioning functions, while the congested side undergoes a period of recovery. Nasal-applied continuous positive airway pressure (n-CPAP) forces air equally up both sides of the nose disrupting the nasal cycle, which could contribute to nasal side-effects, such as nasal dryness, crusting and congestion. The development of a n-CPAP machine, which approximates physiological alternating nasal airflow during sleep, could reduce nasal side effects and improve n-CPAP adherence. A n-CPAP mask would need modification so that air under pressure could be independently directed to and received from each side of the nose. The system would allow for the pre-setting of both the nasal cycle duration time and the degree of airflow partitioning between each naris. A n-CPAP machine that approximates the normal physiological nasal cycle during sleep could reduce the incidence of adverse nasal symptoms and improve sleep quality leading to improved n-CPAP compliance.
Keywords: CPAP; Nasal cycle; Nasal airflow partitioning; Obstructive sleep apnoea